Examining the Capabilities and Challenges of AARON (Painter Software) - Najmedin, Foad; Moghanipour , Majid R. (Actual Problems of Theory and History of Art, 2023)
The present article probes Harold Cohen’s AARON software and its unique features which brings it closer to the definition of “human creativity:, making it distinct from other computer software or basic computer artworks. AARON’s (metaphorically) works are massive images (usually 2.3 meters or even larger murals) in a style and context close to the expressionist literature of the early 20th century. Although features such as linear value and especially coloring were gradually embedded in different versions of AARON, we are mostly faced with linear images (so-called design) in the initial versions. In the early years of the 21st century, he returned to more abstract forms and experienced defining forms, especially more independent coloring. So, it was Cohen’s process of continuous training and his empiricism that made this AI mysterious, fascinating, and exciting at the same time.Here, first, a description of digital and computer art is presented and its characteristics are discussed. Afterward, the artificial intelligence (AI) art and its similarities and differences with human art are addressed using AARON software, and its distinguishing feature, that is the selection in the process of forming the artistic work, is described. Finally, some challenges to this type of art, including the lower quality of the works created by this software, the issue of predestination and free will in its performance, and especially the issue of AARON destiny will be discussed.
Keywords: AARON; Harold Cohen; Artificial Intelligence; AI; computer art